Peri-Urbanization and Land Use Fragmentation in Mexico City. Informality, Environmental Deterioration, and Ineffective Urban Policy - Aguilar, Adrian Guillermo; Flores, Miguel Angel; Lara, Luis Fernando (Frontiers in Sustainable Cities, 2022)
There is a great deal of concern over the scattered, fragmented expansion of cities, particularly in developing countries. This expansion accelerates the peri-urbanization processes expressed in a range of land uses, often with a concentration of the poor in peripheries with an acute shortage of services coupled with profound land-use changes, with far-reaching environmental impacts. The urban periphery is a transition zone, where the urban gradually merges into the rural landscape. It has become heterogeneous from a social, environmental, commercial, and service point of view, reproducing a model of metropolitan inequity with marked socioeconomic inequalities between the center and the periphery. The way these territories are managed is quite far from the road to sustainability. This article seeks to provide an updated analysis of the dynamics of urban expansion and land-use changes on the southern periphery of Mexico City (CDMX) in the Conservation Area (CA), to determine the extent to which a socially segregated, environmentally unsustainable model of urban fragmentation has been reinforced. It also discusses the regulatory, normative framework established in the CA, finding that it has been deficient and implemented in piecemeal fashion. It concludes that local government has failed to provide solutions to reconcile the protection of ecological conservation areas with the needs of the poor in a peri-urban area, thereby reproducing social inequalities in the city. In addition, CDMX land use policy has been ineffective in controlling the expansion of informal human settlements in peri-urban areas with high ecological value.